Early oxidation stages of a Co-Cr-Fe-Mn-Ni-Si complex concentrated alloy with Cr, Mn, and Si contents matching those of 316L stainless steel. (September 2021) - Apell, Jonathan; Wonneberger, Robert; Seyring, Martin; Stöcker, Hartmut; Rettenmayr, Markus; Undisz, Andreas
Graphical abstract: Highlights: CCA with Cr, Mn, and Si contents as 316 L, but 50 % higher configurational entropy. At 400 °C spinel-type, corundum-type, and rock salt-type oxides form. At 800 °C spinel-type and corundum-type oxides form, but spinel is dominant. Configurational entropy does not dominate oxidation behavior. Co and Ni are found in all oxide phases and favor spinel-type oxide formation. Abstract: A complex concentrated Co-Cr-Fe-Mn-Ni-Si alloy with increased configurational entropy and contents of Cr, Mn, and Si corresponding to those in 316L stainless steel was studied with respect to its oxidation behavior. Early-stage oxidation was investigated for annealing at 400 °C and 800 °C. In addition to Cr, considerable amounts of Fe, Co, and Ni were found in the oxide, and nodules formed at 800 °C. In contrast to 316L, on which a protective corundum-type oxide forms during oxidation, the formation of spinel-type oxide was observed to dominate both at low and high temperature.